2015
DOI: 10.1002/ijc.29528
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 expression in fallopian tube epithelium drives cell migration

Abstract: Ovarian cancer is the fifth leading cause of cancer death among US women. Evidence supports the hypothesis that high-grade serous ovarian cancers (HGSC) may originate in the distal end of the fallopian tube. Although a heterogeneous disease, 96% of HGSC contain mutations in p53. In addition, the “p53 signature”, or overexpression of p53 protein (usually associated with mutation), is a potential precursor lesion of fallopian tube derived HGSC suggesting an essential role for p53 mutation in early serous tumorig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 51 publications
2
62
0
Order By: Relevance
“…Murine oviductal cells (MOE) and murine ovarian surface epithelial cells (MOSE) were obtained from Dr. Barbara Vanderhyden at the University of Ottawa. MOE and MOSE cells were cultured as previously described [34]. OVCAR4 cells were obtained from the National Cancer Institute from the Division of Cancer Treatment and Diagnosis Tumor Repository.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Murine oviductal cells (MOE) and murine ovarian surface epithelial cells (MOSE) were obtained from Dr. Barbara Vanderhyden at the University of Ottawa. MOE and MOSE cells were cultured as previously described [34]. OVCAR4 cells were obtained from the National Cancer Institute from the Division of Cancer Treatment and Diagnosis Tumor Repository.…”
Section: Methodsmentioning
confidence: 99%
“…TCM1204) or empty vector with neomycin resistance as previously described [34]. Cells were plated at low density and treated with 0.15 mg/mL of G418 (Gemini bio-products, Woodland, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective analysis found salpingectomy was associated with a 45% decrease in ovarian cancer risk [7]. Our laboratory has shown that murine oviductal epithelial (MOE) cells stably expressing PTEN shRNA , PTEN shRNA +KRAS G12V , or PTEN shRNA +TP53 R273H colonized the ovary following intraperitoneal xenograft [8,9]. Several transgenic mouse models have also been developed that form fallopian tube-derived tumors that spread to the ovary [1012].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that it has recently been demonstrated that Fallopian tube secretory cell expansion and the ratio between secretory/ciliated cells (S/C ratio) are linked to pelvic serous neoplasia [91] and in this scenario the cancer cells of the serous tubal intraepithelial carcinoma (STIC) bearing a “p53 signature” invade onto the ovary and implant on peritoneal surfaces [9294]. During this process, the secretory cells retain the expression of PAX8 that possibly continues to exert its transcriptional activity on its physiological targets and in addition may also function on new targets that become available after the tumorigenic hits (BRCA mutations, p53 signature etc).…”
Section: Discussionmentioning
confidence: 99%